Induction and Superinduction of Serotonin N-Acetyltransferase by Adrenergic Drugs and Denervation in Rat Pineal Organ - Deguchi, Takeo (1972)
Activity of serotonin N-acetyltransferase (EC 2.3.1.5) in rat pineal organ is rapidly and markedly elevated in vivo after administration of β-(3,4-dihydroxyphenyl)-L-alanine (L-DOPA), norepinephrine, epinephrine, isoproterenol, monoamine oxidase inhibitors, or theophylline. Serotonin or 5-hydroxytryptophan has no effect on the increase in activity of this enzyme. Inhibitors of protein synthesis or propranolol, a β-adrenergic blocking agent completely inhibit(s) the increase in activity of serotonin N-acetyltransferase induced by drugs, indicating that new enzyme molecules are formed via stimulation of β-receptors of pineal cells and adenosine 3′:5′-cyclic monophosphate. When rat pineal organ is denervated by ganglionectomy, β-(3,4-dihydroxyphenyl)-L-alanine induces much more serotonin N-acetyltransferase than in the innervated gland. This superinduction by denervation appears to be due to changes of the postsynaptic site, probably the β-adrenergic receptor on the pineal cell.